The Dynamics of Team Learning: Harmony and Rhythm in Teamwork Arrangem ents for Innovation - Harvey, Jean-François; Cromwell, Johnathan R.; Johnson, Kevin J.; Edmondson, Amy C. (Administrative Science Quarterly)
Innovation teams must navigate inherent tensions between different lea rning activities to produce high levels of performance. Yet, we know l ittle about how teams combine these activities—notably reflexive, expe rimental, vicarious, and contextual learning—most effectively over tim e. In this article, we integrate research on teamwork episodes with in sights from music theory to develop a new theoretical perspective on t eam dynamics, which explains how team activities can produce harmony, dissonance, or rhythm in teamwork arrangements that lead to either pos itive or negative effects on overall performance. We first tested our theory in a field study using longitudinal data from 102 innovation te ams at a Fortune Global 500 company; then, we replicated and elaborate d our theory in a study of 61 MBA project teams at an elite North Amer ican university. Results show that some learning activities can occur within the same teamwork episode to have harmonious positive effects o n team performance, while other activities combine to have dissonant n egative effects when occurring in the same episode. We argue that diss onant activities must be spread across teamwork episodes to help teams achieve a positive rhythm of team learning over time. Our findings co ntribute to theory on team dynamics, team learning, and ambidexterity.